Modification of Montmorillonite with Chitosan as Mercury Metal Adsorbent - Julinawati, Julinawati; Nisa, Salasatun; Fathurrahmi, Fathurrahmi; Mustafa, Irfan; Saleha, Sitti; MZ., Kartika; Suryati, Suryati (Universitas Syiah Kuala, 2024)
Modification of montmorillonite with chitosan as an adsorbent of mercury (Hg) metal has been carried out. This study aims to determine the characteristics of the adsorbent, the optimum adsorption capacity of Hg metal, and its adsorption isotherm equation. The optimum conditions for Hg metal adsorption are determined by varying the contact time and pH of the solution. Variations in adsorbate concentration are carried out to determine the adsorption isotherm. Characterization of the adsorbent using FTIR shows the presence of -OH, Si-O, Al-O, C-C, and N-H groups. The optimum conditions for mercury metal adsorption by montmorillonite modified with chitosan occur at a contact time of 80 minutes, and a pH of 4. The adsorption process of mercury metal ions using montmorillonite adsorbent modified with chitosan satisfies both isotherm models, namely the Langmuir and Freundlich isotherms with R2 values of 0.971 and 0.967 respectively, and a maximum adsorption capacity of 13.513 mg/g. The regeneration test showed that the adsorbent can be reused for the absorption of mercury metal ions.